Clinical characteristics and disease course before and after SARS-CoV-2 infection in a large cohort of systemic sclerosis patients - Guler, Aslihan Avanoglu; Ozcimen, Busra; Aydogdu, Mesude Seda; Sari, Alper; Numune, Aliyeva; Ersan, Nazife Tuzun; Tufan, Abdurrahman (Tubitak Scientific & Technological Research Council Turkey, 2024)
Background/aim: The objective of this study is to evaluate the clinical presentations and adverse outcomes of Coronavirus Disease 2019 (COVID-19) in patients with systemic sclerosis (SSc) and assess the impact of SSc features on the clinical course of COVID-19. Materials and methods: In this multicenter, retrospective study, SSc patients with COVID-19 were included. Clinical features of SSc, along with detailed COVID-19 data, were extracted from medical records and patient interviews. Results: The study included 112 patients (mean age 51.4 +/- 12.8 years; 90.2% female). SSc-associated interstitial lung disease (ILD) was evident in 57.1% of the patients. The findings revealed hospitalization in 25.5%, respiratory support in 16.3%, intensive care unit admission in 3.6%, and a mortality rate of 2.7% among SSc patients with COVID-19. Risk factors for respiratory failure, identified through univariate analysis, included ILD (OR: 7.49, 95% CI: 1.63-34.46), >= 1 comorbidity (OR: 4.55, 95% CI: 1.39-14.88), a higher physician global assessment score at the last outpatient visit (OR 2.73, 95% CI: 1.22-6.10), and the use of mycophenolate at the time of infection (OR: 5.16, 95 %CI: 1.79-14.99). Notably, >= 1 comorbidity emerged as the sole significant predictor of the need for respiratory support in COVID-19 (OR: 5.78, 95% CI: 1.14-29.23). In the early post-COVID-19 period, 17% of patients reported the progression of the Raynaud phenomenon, and 10.6% developed new digital ulcers. Furthermore, progression or new onset of dyspnea and cough were detected in 28.3% and 11.4% of patients, respectively. Conclusion: This study suggests a potential association between adverse outcomes of COVID-19 and SSc-related ILD, severe disease activity, and the use of mycophenolate. Additionally, it highlights that having comorbidities is an independent risk factor for the need for respiratory support in COVID-19 cases.
Keywords: Systemic sclerosis; COVID-19; interstitial lung disease; outcome; respiratory support